An Islamic reading of Marie Stopes’ married love - Hasan, Md. Mahmudul (2017)
Marie Carmichael Stopes‟ identity as the pioneer of family planning may come as a shock to many Muslims who regard contraceptive practices as forbidden. Her most influential book Married Love (1918) may cause a double fold negative impression among them as it is both a manual of sexual intercourse and a treatise of birth-control campaign. It puts equal importance on women‟s sexuality and erotic desire – a topic not widely discussed among Muslims in general. Stopes defied cultural conventions and gender norms by talking about sexual relations in a lurid form. She sought to help women “nearly normal” and “either married or about to be married” but “mired in ignorance … in pain and confusion” by way of informing them about female sexual health and orgasmic rights. As she states: “In my first marriage I paid such a terrible price for sex-ignorance that I feel that knowledge gained at such a cost should be placed at the service of humanity.” The book proved highly useful as it provides women with discreet advice about sexual conduct. It “was the most widely read manual of how to practise and achieve companionate marriage” for women to enjoy conjugal life and withstand men‟s sexual abuse. Despite that, upon publication in 1918, its reception among both the Church and the medical establishment in Britain was not very warm or enthusiastic. In today‟s Western society however, information on contraception as well as narratives of sexual experiences and attitudes has made its way into public consciousness. Conversely, even though Islam considers sex in marital relationship as an act of worship and encourages people to marry and not to lead celibate lives, many Muslim societies may regard Married Love as scandalous. Given this theoretical background and the need for a clear distinction between the normative teachings of Islam and the gender norms prevalent in Muslim societies, my paper will see whether or not the content of Married Love goes against Islamic teachings. It will especially look at Stopes‟ concepts of women‟s sexuality and family planning from an Islamic perspective.